Political Emotions Towards a Decent Public Sphere - Brooks, Thom. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
How might political emotions contribute to the creation of a decent public sphere? Our societies are characterized by difference and contestation. Cultivating political emotions can appear counterproductive to stability and peace. But there is an increasing recognition that emotions can be harnessed to empower community cohesion and social justice - and new ideas about how our political emotions can foster a decent public sphere and overcome intolerance are urgently needed. In Political Emotions: Towards a Decent Public Sphere, leading theorists consider the limits and prospects of cultivating our emotions that support social justice. All examine this topic from a diversity of disciplinary perspectives breaking new ground and yielding new understandings. Issues explored include adaptive preferences, capabilities, civil religion, compassion, conscience, dignity, feminism, imagination, multicultural citizenship, perfectionism, political liberalism, public sentiments, sympathy and much more in a wide-ranging exploration of key themes in contemporary political philosophy - and Martha C. Nussbaum's significant contributions to it in particular - that should be of interest to anyone working in these broad areas.
Introduction -- Political Objectivity -- Envy as a Civic Emotion -- How the Body Is Involved in Moral and Cognitive Emotions -- Conscience and Context -- The Politics of Compassion -- Cultivating Citizenship: On the Importance of Stakeholding -- The Liberalism of Love -- Perfectionist Liberalism or Political Liberalism? How Might Amartya Sen Respond to Martha Nussbaum's Question? -- The "Transition" to Restorative Justice -- Reply.
Keywords: Social sciences-Philosophy.; Political science-Philosophy.; Ethics; Social Philosophy; Political Philosophy; Moral Philosophy and Applied Ethics